2019
DOI: 10.3390/en12234556
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Diagnostics of Natural Ventilation in Buildings: An Integrated Approach

Abstract: Diagnostics of natural ventilation in buildings is problematic, as the airflow rate changes considerably over time. One constant average airflow is usually assumed when calculating energy demand for a building, however, such a simplification could be fraught with considerable error. The paper describes a comprehensive methodology for the diagnostics of a natural ventilation system in a building and its practical application. Based on in situ measurements and simulations in two existing buildings (dwelling hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…in New York found that crowded home environments-a typical feature of poor neighborhoods-raised the risk of airborne disease transmission in pregnant women (Emeruwa et al 2020). In some studies, crowded neighborhoods had higher transmission rates than less crowded neighborhoods (Kadi and Khelfaoui 2020;Zhang and Schwartz 2020)-a pressing challenge in such cities as Mumbai, Nairobi, and Karachi, where substantial portions of the city consist of slums.…”
Section: Features Of the Built Environment That Increase Disease Riskmentioning
confidence: 99%
“…in New York found that crowded home environments-a typical feature of poor neighborhoods-raised the risk of airborne disease transmission in pregnant women (Emeruwa et al 2020). In some studies, crowded neighborhoods had higher transmission rates than less crowded neighborhoods (Kadi and Khelfaoui 2020;Zhang and Schwartz 2020)-a pressing challenge in such cities as Mumbai, Nairobi, and Karachi, where substantial portions of the city consist of slums.…”
Section: Features Of the Built Environment That Increase Disease Riskmentioning
confidence: 99%
“…Several contributions have been devoted to this issue, focused on natural air exchange, in the recent period [41][42][43][44]. In paper [45], the focus is on air exchange in the summer when considering energy savings.…”
Section: Measurement Of Carbon Dioxide Concentration Valuesmentioning
confidence: 99%
“…V inf -infiltration airflow, m 3 /s, ELA -effective leakage area at 4 Pa pressure differential, cm 2 , C s -coefficient for stack-induced infiltration, 0.00029 (dm 3 /s) 2 /(cm 4 K), ΔT -temperature diff erence between zone air and outdoor air, K, C w -coefficient for wind-induced infiltration, 0.000231 (dm 3 /s) 2 /(cm 4 (m/s) 2 ), w -local wind speed, m/s. For calculations as the leakage areas were adopted: C -flow coefficient, m 3 /(hPa 0.67 ), a -airtightness factor, m 3 /(mhPa 0.67 ), l -length of the window leakages, m. The value of the airtightness factor for the windows was assumed at the level of 0.3 m 3 /(mhPa 0.67 ) based on available studies on the airtightness of Polish residential buildings [21,22]. The length of the window leakages was the total perimeter of each window sash.…”
Section: Methodsmentioning
confidence: 99%